Development of Digestive Ludo Learning Media to Improve Student Learning Outcomes - A.A. Bagus Tri Rama Antara; Rusdarti Rusdarti; Barokah Isdaryanti (Journal of Primary Education, 2024)
The learning process in the classroom often causes boredom in students, which has an impact on low student learning outcomes; this is evident from the results of initial observations at elementary schools in Cluster II, Jembrana District, which showed that the learning outcomes of IPAS for grade V students were still low. The purpose of this study was to develop Ludo learning media in learning IPAS on the human digestive system in grade V elementary schools, to analyze the feasibility and effectiveness of ludo digestion learning media to improve the learning outcomes of IPAS for grade V elementary school students. This study used the research and development (R&D) method with the ADDIE model. The data collection techniques used were interview, observation, questionnaire, test, and documentation. The validation results of the ludo digestion learning media were considered very feasible, with an average percentage of 97.92% in the material validation test and 92.50% in the media validation test. The ludo digestion learning media is also effective in improving the learning outcomes of IPAS for grade V elementary school students, as reviewed by a 2-tailed significance value of 0.000 and an n-gain value of 0.73. Based on these results, it can be concluded that the digestive Ludo learning media is feasible and effective for improving student learning outcomes in IPAS learning for grade V on the human digestive system material at elementary schools in Cluster II, Jembrana District.